The statistical study of robots manipulators - Galhano, Alexandra (2019)
A new approach to the analysis and design of robot manipulators is presented. The novel feature resides on a non-standard formulation to the modelling problem. Usually, system descriptions are based on a set of differential equations which, due to their nature lead to very precise results and strategies but, in general, require laborious conputations. This motivates the need of alternative models based on other mathematical concepts. The proposed statistical method gives clear guidelines towards the robot kinematic and dynamic optimization. Furthermore, the results point out structural characteristics of the trajectory planning algorithm as well as ideal-actuator properties.